(untitled) (Comprehensive Journal of Science, 2025)
The study aimed at identifying the most prominent challenges facing local radio stations in the city of Derna in light of the digital transformation and analyzing the economic reality of local radio stations in light of the digital transformation, and revealing the mechanisms of adaptation to new digital revenue models. It also aimed to provide scientific proposals that contribute to the survival and development of local radio stations. The study also relied on the descriptive analytical approach through the questionnaire distributed to a sample of (16) employees in local radio stations in the city of Derna (Derna Local Radio, Derna National Radio, Sama Radio), and the results found that the major platforms (google,meta) It has taken over a large part of the budgets of local advertising, and thus the direct impact on the revenues of these radio stations, despite the fact that they retain competitive advantages such as the confidence of the local public and local identity ( such as spatial identity and dialect). The results also showed the need for cadres to train and also to modernize the infrastructure. The current revenue models are useless and not sufficient to achieve financial sustainability. The study also recommended developing the way local radio stations work from traditional methods to moving towards comprehensive media institutions through the events of some changes, such as providing electronic applications on mobile phones and providing sources of income through media training. Strengthening partnerships with local community institutions, in order to ensure survival in the modern digital environment.